Low dimensional organic metal-halide hybrids : molecular design & optoelectronic properties - Febriansyah, Benny (Nanyang Technological University, 2020)
Low-dimensional (LD) hybrid metal-halide (perovskite) materials can be induced through incorporation of more hydrophobic, moderately-sized organic cations. This not only provides improved stability against degradation by moisture and oxygen relative to their three-dimensional (3D) counterparts, but also affords significant room for materials exploration and engineering. Although the number of reports on LD hybrids in the literature is numerous, systematic studies on the effect of cation structure towards the materials’ final structures are still relatively scarce. LD hybrids are, generally, considered ill-suited for photovoltaic applications due to their reduced dimensionality manifests in compromised visible light absorption and poor charge transport. Furthermore, the strengthened binding energy and oscillator strength of the electron-hole pairs (excitons) in the LD system concomitantly result in increased radiative decay rates, which lead to typical narrow emissions. Motivated by these circumstances, this dissertation uses targeted molecular approach as a strategy to modulate the physical properties of such extended solid materials. Specifically, organic cations are rationally designed to target desired metal-halide structures at molecular level. As a result, the formability of such structures can be systematically investigated. More importantly, the resulting “molecularly-engineered” materials can be notably endowed with optoelectronic properties suitable for photovoltaic and solid-state lighting applications. Firstly, using pyridinium core as the framework, empirical understanding of molecular features that induce formation of two-dimensional (2D), one-dimensional (1D), and trimeric lead-halide hybrid materials formation can be gleaned. Primary ammonium groups (-NH3+) are found to be a prerequisite for formation of 2D perovskites, presumably due to the highly localized charge density and limited steric bulk of this functionality. In the absence of -NH3+, 1D iodoplumbate inorganic architectures are obtained with comparatively short and flexible N-alkyl substituents (e.g. ethyl, propyl, and pentyl). The presence of N-alkyl substituents containing neutral hydrogen bond donors (e.g. alcohol, carboxylic acid, and primary amide functionality) did not change this outcome and the 1D structures were retained. When more rigid substituents are employed (e.g. benzyl, acetamidyl, and cyanomethyl), hybrids composed of very rare face-sharing inorganic trimers can be afforded. Secondly, systematic tuning of the aromatic ring size and position of -NH functionalities lead to the discovery of the unprecendented corrugated “3 × 3” (110)-oriented 2D lead-iodide and tin-iodide perovskites (where “n × n” refers to the number (n) of contiguous metal-halide octahedra comprising each ridge). The main driving force to formation of the unusual structure is attributed to the presence of a coulombic interaction that occurs perpendicular to the plane of the heterocyclic ring. With similar approach, a rare white-light emitting “2 × 2” (110)-oriented 2D lead-bromide perovskite (CIE coordinates of (0.32, 0.41), correlated colour temperature (CCT) of 5824 K and colour rendering index (CRI) of 73) with significance in solid-state lighting applications can also be obtained. From photovoltaic application point of view, we demonstrate for the first time that 1D lead iodide materials can be endowed with extended light absorption (up to 800 nm), reduced band gaps (1.74 eV to 1.77 eV) and enhanced photoconductivity. This is achieved by employing viologen cations endowed with hydrogen bonding functionalities that are capable of inducing π-π stacking, such that charge transfer interaction between the organic and inorganic lattices are reinforced. In addition, we also show new 2D perovskites exhibiting reduced band gaps (2.35 – 2.46 eV), relaxed dielectric confinement (excitonic binding energies of 130 – 200 meV), and improved electrical and photoconductivities (more than 10-fold) relative to conventional 2D lead-iodide perovskites. Such features can be realized by reducing their inorganic inter-octahedral distortions (largest Pb-(μ-I)-Pb bond angles of 170 – 179°) and inorganic layers separation (shortest I···I contacts ≤ 4.278 – 4.447 Å). At the time it was published, these features eventually afforded the world record power conversion efficiencies for pure 2D perovskite solar cells of 1.43 and 1.83%. From solid-state lighting application point of view, in addition to the discovery of a rare “2 × 2” (110)-oriented 2D lead-bromide perovskite, we demonstrate for the first time that white-light emission can be also be induced from (100)-oriented 2D compound with deformed lead-bromide coordination geometry (i.e. high degree of intra-octahedral distortion), while featuring mild inter-octahedral tilting. This is achieved by incorporating sterically-demanding organic cations, such as that with piperidinium core, where the resulting compound is shown to exhibit emission with CIE coordinates of (0.38, 0.38), CCT of 4088 K and CRI of 96. Furthermore, we also report three new compounds containing very rare lead-bromide trimers templated by pyridinium cations functionalized with rigid substituents. The compounds feature intrinsic, highly stoke-shifted (ca. 1.39 eV), ultrabroadband (full width at half maximum of ca. 540 meV), and efficient photoluminescence properties (PLQY of at least 10%), all of which serve as a powerful proof of concept of inorganic lattice control by the organic molecular structure.